Perbadingan Faktor Resiko Perilaku Seksual Beresiko Remaja Pedesaan dan Perkotaan di Indonesia - Ahmad Dahlan Syam; Sigit Mulyono Mulyono (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the comparison of risk factors for risky sexual behavior in rural and urban adolescents. The method used is Literature Review using the request database, Springer Link and Google Scholar. The results of the study, there were six articles that were analyzed and provided an overview of the risk factors for risky sexual behavior in adolescents in rural and urban areas. The risky sexual behavior of female adolescents in urban areas who have had sexual intercourse is higher than in rural areas, but male adolescents are higher in rural areas than in urban areas. Peer factors are also a trigger for risky sexual behavior in adolescents in rural and urban areas. Lifestyle factors such as drinking alcohol and using narcotics in rural areas are more associated with lifestyles of drinking alcohol and smoking than adolescents in urban areas, while consuming illegal drugs is the most common thing in urban areas. The information exposure factor in rural areas is still very low compared to urban areas. In conclusion, there are several factors that influence adolescents in rural and urban areas to engage in risky sexual behavior including; gender, peer factors, the presence of parents and community figures and lifestyle. Keywords: Risky Sexual Behavior, Urban and Rural, Adolescents